Development of a Multi-Channel Ultra-Wideband Electromagnetic Transient Measurement System - Shaoyin He; Xiangyu Chen; Bohao Zhang; Liang Song (Sensors)
In complex electromagnetic environments, such as substations, converter stations in power systems, and the compartments of aircraft, trains, and automobiles, electromagnetic immunity testing is crucial. It requires that the electric field sensor has features such as a large dynamic measurement range (amplitude from hundreds of V/m to tens of kV/m), a fast response speed (response time in the order of nanoseconds or sub-nanoseconds), a wide test bandwidth (DC to 1 GHz even above), miniaturization, and robustness to strong electromagnetic interference. This paper introduces a multi-channel, ultra-wideband transient electric field measurement system. The system’s analog bandwidth covers the spectrum from DC and a power frequency of 50 Hz to partial discharge signals, from DC to 1.65 GHz, with a storage depth of 2 GB (expandable). It overcomes issues related to the instability, insufficient bandwidth, and lack of accuracy of optical fibers in analog signal transmission by using front-end digital sampling based on field-programmable gate array (FPGA) technology and transmitting digital signals via optical fibers. This approach is effectively applicable to measurements in strong electromagnetic environments. Additionally, the system can simultaneously access four channels of signals, with synchronization timing reaching 300 picoseconds, can be connected to voltage and current sensors simultaneously, and the front-end sensor can be flexibly replaced. The performance of the system is verified by means of a disconnect switch operation and steady state test in an HVDC converter station. It is effectively applicable in scenarios such as the online monitoring of transient electromagnetic environments in high-voltage power equipment, fault diagnosis, and the precise localization of radiation sources such as partial discharge or intentional electromagnetic interference (IEMI).